2022
DOI: 10.1063/5.0109549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface temperature on quantum dynamics of D2 on Cu(111) using a chemically accurate potential energy surface

Abstract: The effect of surface mode vibrations on the reactive scattering of D2, initialized in the ground rovibrational state (v = 0, j = 0), from a Cu(111) surface is investigated for different surface temperature situations. We adopt a time and temperature dependent effective Hamiltonian [J. Chem. Phys. 154, 104103 (2021)] constructed by combining the linearly coupled many oscillator model [J. Chem. Phys. 136, 084306 (2012)] and the static corrugation model [J. Chem. Phys. 137, 054703 (2012)] potential within the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 123 publications
(366 reference statements)
2
3
0
Order By: Relevance
“…Taking into account the uncertainty in absolute experimental saturation values, due to the nature of the direct inversion of desorption results used in the experimental method, we also found excellent agreement between our (QD-)EAM-SCM results and the experimental curves published by Rettner et al, 7 Hodgson et al 8 and Kaufmann et al 11 Even for the curve onset, where reaction is best plotted on a logaritmic scale, we see good overlap with our theoretical results. At very low incidence energies, our QD results even indicate a small upturn in reaction similar to those found by Kaufmann et al, also found by Dutta et al using their EfHP method and the same QD code, 29 but not before been reported in any other theoretical works. However, great care should be taken when interpreting our QD results in this regime, as the very low probabilities involved enables the noise inherent Accepted to J. Chem.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Taking into account the uncertainty in absolute experimental saturation values, due to the nature of the direct inversion of desorption results used in the experimental method, we also found excellent agreement between our (QD-)EAM-SCM results and the experimental curves published by Rettner et al, 7 Hodgson et al 8 and Kaufmann et al 11 Even for the curve onset, where reaction is best plotted on a logaritmic scale, we see good overlap with our theoretical results. At very low incidence energies, our QD results even indicate a small upturn in reaction similar to those found by Kaufmann et al, also found by Dutta et al using their EfHP method and the same QD code, 29 but not before been reported in any other theoretical works. However, great care should be taken when interpreting our QD results in this regime, as the very low probabilities involved enables the noise inherent Accepted to J. Chem.…”
Section: Discussionsupporting
confidence: 92%
“…Recent work by Dutta et al report a similar upturn for the D 2 /Cu(111) system, investigated with the same SRP48 BOSS PES and QD implementation, but using the effective Hartree potential method to include surface temperature effects. 29 They believe this could be attributed to vibrational degrees of freedom, due to a modeled elevated surface temperature, which could match the slow channel as reported by Kauf- mann et al 11 This EfHP work, however, uses the same SPO propagation method and is thus also expected to exhibit errors of a similar magnitude as our work, which is covered in both works. Furthermore, we also observe an upturn for the ideal lattice BOSS model, which suggests something more than purely attributing this to surface vibrational DoF.…”
Section: Logscale Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…12,27 Several theoretical works have also recently been published, with Dutta et al presenting their work on the effective Hartree potential (EfHP) approach to include surface temperature effects into the H 2 on Cu(111) model at a) Electronic mail: m.somers@chem.leidenuniv.nl a quantum dynamical level. 28,29 Zhu et al demonstrated that an atomistic neural network potential (NNP), with the surface degrees of freedom (DoF) included, can be constructed for several facets of the Cu surface, using only a limited data set. 21 Smits et al demonstrated surface temperature effects could be accurately included into 6D quantum dynamical (QD) simulations for the rovibrational ground state of H 2 on Cu(111) using the static corrugation model (SCM), 26 and at a quasi-classical (QC) level for a range of rovibrational states of D 2 on Cu(111).…”
Section: Introductionmentioning
confidence: 99%